Consideraţii asupra sistemului de aşezări din judeţul Iaşi - Daniela Iurea (Urbanism. Arhitectura. Constructii, 2011)
The dynamics and configuration of the settlement system in Iași County have directly influenced its social and economic development. This paper highlights the main characteristics of the present settlement system in Iași County. The analisys focuses on the structure, number, density, territorial distribution, size, dynamics, and functional typology of rural and urban settlements. It alsoidentifies the main disfunctionalities of the settlements system of Iași County and provides some recommendations to overcome these problems.